Pengembangan Multimedia Interaktif Berbasis Problem Based Learning (PBL) untuk Meningkatkan Minat dan Hasil Belajar Siswa Sekolah Dasar - Hanin Nalinda; Mintarsih Arbarini; Harianingsih Harianingsih (Pusat Riset dan Inovasi Nasional, 2025)
The learning media currently used is still dominated by textbooks and pictures, while the application of innovation in science learning has not been optimized. This study aims to identify the needs, development stages, feasibility level, and effectiveness of interactive multimedia based on Problem Based Learning (PBL) in increasing the interest and learning outcomes of elementary school students. This research uses the Research and Development (R&D) method with the ADDIE model approach. The research subjects included media experts, material experts, and 25 students of class IV-D and 25 students of class IV-C at SD IT Cahaya Bangsa. Data collection techniques were carried out through documentation, questionnaires, observation, and interviews, with instruments in the form of questionnaires and evaluation questions. Data analysis was done descriptively qualitative and quantitative. The research findings show that PBL-based interactive multimedia qualifies as learning media that is suitable for use. The validation results from material experts and media experts both showed a “very feasible” category. The effectiveness test shows the difference between the pretest and posttest results, with the N-gain value in the medium category. Similarly, the increase in student interest in learning can be seen from the difference in questionnaire scores before and after learning, which also shows a moderate category in the N-gain test. Overall, PBL-based interactive multimedia is proven to be very feasible as a supporting media in science learning and is quite effective in increasing the interest and learning outcomes of grade IV elementary school students.